SPE/DOE Improved Oil Recovery Symposium 2000
DOI: 10.2118/59287-ms
|View full text |Cite
|
Sign up to set email alerts
|

Simulating Foam Processes at High and Low Foam Qualities

Abstract: fax 01-972-952-9435. AbstractFoams used for gas or acid diversion exhibit two flow regimes, depending on foam quality. Two foam simulators, one the most widely used commercial foam simulator and the other developed at our university, fit steady-state foam behavior in both regimes. A simple procedure is described for fitting simulator parameters to a set of steady-state coreflood data and examples are shown. Fitting model parameters to a single coreflood data can err by fitting this datum to the wrong flow regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
91
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 152 publications
(93 citation statements)
references
References 40 publications
2
91
0
Order By: Relevance
“…In our current work, the surfactant concentration and dry-out effects are considered and some typical values are chosen, as shown in Table 1. Here, we chose 100 for fmmob, which is less than these employed by earlier researchers, such as 1000 (Rossen et al 2006), 3000 (Rossen and Shen 2007;Jamshidnezhad et al 2008a), or 5000 (Cheng et al 2000;Rossen and Renkema 2007;Kloet et al 2009), because we believe too strong foam used previously masked some details in the foam process, which is crucial for the novel foam. Meanwhile, it is also much less than the result of coreflood matching (Ma et al 2013) because the foam in 3D is much weaker than in 1D, which has been demonstrated by Li et al (2006).…”
Section: Reservoir Modelmentioning
confidence: 99%
“…In our current work, the surfactant concentration and dry-out effects are considered and some typical values are chosen, as shown in Table 1. Here, we chose 100 for fmmob, which is less than these employed by earlier researchers, such as 1000 (Rossen et al 2006), 3000 (Rossen and Shen 2007;Jamshidnezhad et al 2008a), or 5000 (Cheng et al 2000;Rossen and Renkema 2007;Kloet et al 2009), because we believe too strong foam used previously masked some details in the foam process, which is crucial for the novel foam. Meanwhile, it is also much less than the result of coreflood matching (Ma et al 2013) because the foam in 3D is much weaker than in 1D, which has been demonstrated by Li et al (2006).…”
Section: Reservoir Modelmentioning
confidence: 99%
“…Parameter fmcap should be set to the smallest capillary number expected to be encountered by foam in the simulation (Cheng et al, 2000;Boeije and Rossen;, and epcap represents the extent of shear-thinning behavior. Newtonian behavior corresponds to epcap = 0 and positive epcap to shearthinning behavior.…”
Section: Implicit-texture Foam Modelmentioning
confidence: 99%
“…We have modified the procedure explained by Ma et al (2013Ma et al ( , 2014 by adding shear-thinning function because in their approach smaller values can be assigned to epdry, although as shown later choosing very large values of epdry (as described by Cheng et al, 2000;Boeije and Rossen, 2013), does not alter the general conclusions of this paper. The procedure used here, described in Appendix B, seeks a least-squares fit to all the app f  data subject to weighting and constraints supplied by the user.…”
Section: Implicit-texture Foam Modelmentioning
confidence: 99%
See 2 more Smart Citations